Review of The Forest and the EcoGothic - Bagi, Dániel (AMERICANA E-journal of American Studies in Hungary, 2021)
The Forest and the EcoGothic: The Deep Dark Woods in the Popular Imagination Elizabeth Parker 2020. Cham, Switzerland: Palgrave Macmillan ix+308 pages ISBN 978-3-030-35153-3, 978-3-030-35154-0 (eBook)